POSSIBILITIES OF INCLUSIVE TOURISM DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article analyzes the development of tourism sectors, including inclusive tourism, and its impact on the rise of the international image of Uzbekistan.Also, the issues of social rehabilitation of citizens with limited opportunities and disabilities in the life of the society, and the importance of inclusive tourism in their socialization into the life of the society are covered.